2005
DOI: 10.1091/mbc.e05-04-0354
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 6 Regulates Human Immunodeficiency Virus Type 1 Infection

Abstract: Efficient human immunodeficiency virus (HIV)-1 infection depends on multiple interactions between the viral gp41/gp120envelope (Env) proteins and cell surface receptors. However, cytoskeleton-associated proteins that modify membrane dynamics may also regulate the formation of the HIV-mediated fusion pore and hence viral infection. Because the effects of HDAC6-tubulin deacetylase on cortical ␣-tubulin regulate cell migration and immune synapse organization, we explored the possible role of HDAC6 in HIV-1-envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(233 citation statements)
references
References 57 publications
11
220
2
Order By: Relevance
“…Then, the subcellular localization of CD81 and CD4 was studied in T lymphocytes exposed to HIV-1 and during syncytia formation. We found that in CEM 1.3 cells and T lymphoblasts exposed to HIV-1 virions, CD4 and CD81 were concentrated at the area of viral contact, a phenomena called capping (38,42) (Fig. 1C and data not shown).…”
Section: Cd81 Localizes At Cellular Contacts During Syncytia Formatiomentioning
confidence: 81%
See 1 more Smart Citation
“…Then, the subcellular localization of CD81 and CD4 was studied in T lymphocytes exposed to HIV-1 and during syncytia formation. We found that in CEM 1.3 cells and T lymphoblasts exposed to HIV-1 virions, CD4 and CD81 were concentrated at the area of viral contact, a phenomena called capping (38,42) (Fig. 1C and data not shown).…”
Section: Cd81 Localizes At Cellular Contacts During Syncytia Formatiomentioning
confidence: 81%
“…HIV-1 NL4.3 entry and infection were assayed in HeLa P5 cells as described previously (38). Briefly, HIV-1 NL4.3 infection of HeLa P5 cells was conducted in 96-well plates for 5 h at 37°C.…”
Section: Hiv-1 Entry and Infectionmentioning
confidence: 99%
“…Indeed, cytoskeleton-dependent functions of HDAC6 have been shown to be crucial in HIV-1 infection of CD4 þ cells. An HDAC6-dependent increase in tubulin acetylation occurs following HIV-1 Env-CD4 receptor interaction in the CD4 þ cells, which could be an important event in HIV-1 cell fusion and infection (Valenzuela-Fernandez et al, 2005). Accordingly, HDAC6 downregulation or the inhibition of its catalytic activity by a specific drug significantly stimulates HIV-1 infection (Valenzuela-Fernandez et al, 2005).…”
Section: Hdac6: a Therapeutic Target?mentioning
confidence: 99%
“…HDAC6 also has important roles in some viral infections. The internalization of human immunodeficiency virus (HIV) is regulated by HDAC6, and its overexpression and subsequent deacetylation of MTs inhibited the HIV infection process (Valenzuela-Fernandez et al, 2005). ASFV viral replication factories distinctly resemble aggresomes (Heath et al, 2001), and as such it is possible that manipulation of HDAC6, not changes in MT stability, leads to the hyperacetylation of MTs after ASFV infection.…”
Section: Ad Infection Increases Levels Of Posttranslationally Modifiementioning
confidence: 99%